2007
DOI: 10.1016/j.asr.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of oxidative stress in mediating the effect of altered gravity on the developing rat cerebellum

Abstract: We have previously reported that perinatal exposure to hypergravity affects cerebellar structure and motor coordination in rat neonates. In the present study, we explored the hypothesis that exposure to hypergravity results in oxidative stress that may contribute to the decrease in Purkinje cell number and the impairment of motor coordination in hypergravity-exposed rat neonates. To test this hypothesis we compared cerebellar oxidative stress marker 3-nitrotyrosine (3-NT; an index of oxidative protein modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…An increase in cerebellar oxidative stress was also observed in rats exposed to hypergravity during the perinatal period (Sajdel-Sulkowska et al 2007). …”
Section: Cerebellar Development Under Altered Gravitymentioning
confidence: 89%
See 1 more Smart Citation
“…An increase in cerebellar oxidative stress was also observed in rats exposed to hypergravity during the perinatal period (Sajdel-Sulkowska et al 2007). …”
Section: Cerebellar Development Under Altered Gravitymentioning
confidence: 89%
“…The increased oxidative stress following hypergravity exposure may contribute to the decrease in Purkinje cell number and consequently the decreased motor behavior in hypergravity-exposed rats (Sajdel-Sulkowska et al 2007). Other studies (Raymond et al 2000) showed that under altered gravity, the gravity sensors develop normally, but the connections within the vestibular nuclei and the cerebellum are affected.…”
Section: Cerebellar Development Under Altered Gravitymentioning
confidence: 98%
“…Indeed, microgravity presents a significant hazard to space flight crews throughout the course of missions and could potentially lead to long-term decrements in quality of life (19). Studies have shown that both microgravity encountered by astronauts in space, as well as modeled microgravity on Earth, can induce many deleterious physiological effects including changes in brain structure and function (20). As with radiation, one of the mechanisms involved in the response to spaceflight is oxidative stress (21,22).…”
Section: Introductionmentioning
confidence: 98%
“…A study in rats suggests that cardiomyocytes of rats exposed at +10 Gz for 5 min showed damaged mitochondrial ultrastructure, impaired mitochondrial respiratory chain, decreased content of antioxidant proteins, and increased oxidative stress [ 34 ]. A study in rats suggested that hypergravity influenced the development of the brain through increased oxidative stress on Purkinje cells [ 35 ]. Rats exposed to short (30 sec) +10 Gz stress showed increased brain lipid peroxidation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%